Intuition, imagination, and philosophical methodology - Gendler, Tamar (Oxford : Oxford University Press, 2010)
Tamar Gendler draws together a series of essays in which she investigates philosophical methodology, and shows the value for philosophy of empirical psychology. Three intertwined themes run through the volume: imagination, intuition and philosophical methodology.
Includes bibliographical references.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Thought and thinking -- Philosophy; Imagination (Philosophy); Intuition -- Philosophy; Methodology